Student Perceptions of the Implementation of Ecampus in Islamic Religious Education Departments in Higher Education - Sutrisna, Sutrisna; Nursikin, Mukh; Pratama, Yoga Anjas; Zuraida, Zuraida; Irawan, Dodi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
The internet and all technological devices are currently an inseparable part of education and teaching, for this reason higher education institutions have a high enthusiasm for developing the use of technology in learning activities. The aim of this research was to increase knowledge for students and lecturers in the proper and correct use of Ecampus. The research method used is quantitative using interview and survey techniques. The results of this research show that student understanding increases when students' perceptions of the implementation of Ecampus in the Islamic religious education department in higher education are implemented. The conclusion of this research explains that Ecampus is very useful for students and lecturers in the learning process, especially in learning Islamic religious education in universities so that students can achievegcreativeAndproduce students who excel in using Ecampus. Therefore, in this research, the researcher only conducted research on student perceptions of the implementation of Ecampus in the Islamic religious education department in universities. The researcher hopes that future researchers can conduct research on student perceptions of the implementation of Ecampus in universities in the departmentWhichother.